Secondary Solid Cancers in Patients with Philadelphia Chromosome-Negative Myeloproliferative Neoplasms: A Multicenter Study - Fehmi Hindilerden; Özge Nuran Akay; Elif Aksoy; Aynur Daglar Aday; Emine Gültürk; Meliha Nalçacı; İpek Yönal Hindilerden (Turkish Journal of Hematology)
Objective: We investigated the occurrence and characteristics of secondary solid cancers (SSCs) in patients with Philadelphia chromosome-negative myeloproliferative neoplasms (Ph- MPNs) from Türkiye. We identified the potential risk factors for SSC development, including the impact of cytoreductive therapies, and we assessed the influence of SSC on patient survival. Materials and Methods: A total of 1013 Ph- MPN patients diagnosed between 1995 and 2022 were retrospectively analyzed. Data related to demographics, clinical and laboratory parameters, SSC development, cytoreductive therapy exposure, and survival outcomes were collected. Statistical analyses were performed using IBM SPSS Statistics 26.0. Results: Of the analyzed Ph- MPN patients, 6.6% developed SSC, with carcinoma being the most common type. Older age at the time of Ph- MPN diagnosis and male sex were associated with SSC occurrence. Ph- MPN patients diagnosed with SSC and patients with no diagnosis of SSC showed no significant difference in complete blood count results, spleen size, Ph- MPN diagnostic groups, or driver mutation frequencies. However, patients with SSC had a higher frequency of arterial thrombosis and a tendency towards an increased rate of total thrombosis (p=0.030 and p=0.069, respectively). In multivariate analysis, arterial thrombosis was the sole independent risk factor and interferon (IFN)-based therapy was the sole protective factor for SSC development. Median overall survival (OS) did not differ between patients with and without SSC except for polycythemia vera patients with SSC, who had shorter OS (175±15 versus 321±26 months, respectively; p=0.005). Conclusion: This study highlights the prevalence and characteristics of SSCs in Turkish patients diagnosed with Ph- MPNs. Arterial thrombosis was associated with increased SSC risk while IFN-based therapy offered potential protection from SSC. Screening for SSC in Ph- MPN patients with arterial thrombosis may be valuable. These findings emphasize the importance of malignancy screening in Ph- MPN patients, especially in high-risk subgroups, and call for further research to elucidate the underlying mechanisms and optimize treatment strategies.